HYGIENIC ASSESSMENT OF THE LABOR PROCESS OF WORKERS IN THE SHOE INDUSTRY - Azizova, F.L; Boltaboev, U.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
hygienic assessment of the working conditions of employees of shoe production on the basis of determining the main indicators of the severity of labor and the intensity of the process. Material and methods: studies were conducted among 41 employees of 4 main workshops of the Fergana shoe production in the dynamics of the working day: before work began (800 hours); after the lunch break (1100 hours), before the end of the work (1500 hours). Time observations were conducted in the main professional groups. Results: according to the obtained results, it was found that workers of the shoe production assigned an average of 65.3 to 80.0% of the working time for the main work, while for auxiliary operations from 7.3% to 23.0%, besides, 6.2% and 1.2% of the time is spent on identifying the causes of technological failures and other distracting operations. Conclusions: the irrational mode of labor and the distribution of the main technological operations of production workers, leads to early body fatigue, stagnation in production, reduced productivity of labor.